Atributos químicos, físicos e biológicos do solo em sistemas de uso da terra em Marabá, no sudeste do Pará - Ribeiro, Sandro Barbosa (2021)
Changes in soil attributes are caused by the conversion of native forest systems to agricultural use systems in the Amazon, and attribute assessments help in monitoring the conservation of tropical soils. The objective of this work was to evaluate the land use systems and the consequent changes caused by the management on the chemical, physical and biological attributes of the soil in comparison with these attributes under natural soil conditions in the municipality of Marabá, in the southeast of the state of Pará. The systems evaluated were native forest, agroforestry system, fruit culture and crop-livestock interaction. For the evaluation of soil attributes, 12 composite soil samples were collected in each system, totaling 48 samples. The evaluation of the obtained data was carried out through multivariate analysis and exploratory data analysis through the mean values and the coefficient of variation. The conversion of native forest into land use systems negatively impacted the chemical, physical and biological attributes of the soil. The multivariate analysis techniques separated the native forest and agroforestry systems from the fruit-growing and crop-livestock interaction systems according to the chemical, physical and biological attributes of the analyzed soil. The fruit growing systems and crop-livestock interaction promoted lower results for pH, nitrogen, phosphorus, potassium, calcium, magnesium, organic carbon and macroporosity, in addition to higher aluminum content and higher soil density in relation to native forest. All evaluated land use systems showed a decrease in microbial biomass carbon, basal respiration and microbial quotient, and the crop-livestock interaction system showed an increase in the metabolic quotient in relation to forest. The land use system most similar to native forest was the agroforestry system.